Connections between Certain Subclasses of Analytic Univalent Functions Based on Operators - Ezhilarasi, R.; Sudharsan, T. V.; Haji Mohd, Maisarah; Subramanian, K. G. (Hindawi Publishing Corporation, 2017)
In this paper, by applying the Hohlov linear operator, connections between the class SD(